Education and Unemployment: A French-German Comparison - Charlotte Lauer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
This paper analyses the link between educational attainment and unemployment risk in a French-German comparison, based on a discrete time competing risks hazard rate model applied to comparable microdata sets. The unemployment risk is broken down into the risk of entering unemployment and the risk, once unemployed, of not getting reemployed. The paper examines the impact of education on both risk components. France faces a higher unemployment rate than West-Germany, due to a higher risk of entering unemployment whereas the risk, when unemployed, of not getting reemployed is lower than in Germany. The risk of entering unemployment is particularly high for French employees with poor education, but higher education graduates face a higher risk of getting unemployed in Germany than in France. Concerning the reemployment prospects of the unemployed, they are better in France than in West-Germany at all education levels, but particularly for the unemployed with a low education level. The effect of education on both risk components does not differ significantly across genders, all else equal.
Keywords: J6; I2; 330; Education; unemployment; hazard rate model; Bildungsniveau; Arbeitslosigkeit; Risiko; Mikroökonometrie; Schätzung; Vergleich; Frankreich; Deutschland